Клінічний випадок гіперальдостеронізму - Бурдо, І. С.; Іванова, Н. В.; Шматко, Л. Л. (Clinical Endocrinology and Endocrine Surgery, 2008)
In this article the clinical case of hyperaldosteronism in the patient K. that suffered from hypertension over 20 years. In the results of clinical and laboratory tests in patient K. diagnosis of spontaneous hyperthyroidism, hypercorticalism and Parhon syndrome were consequently excluded. At last the hyperaldosteronism was detected which is most likely secondary against the kidney disease background.